Multicriteria assessment of landscape architecture projects: the sustainability perspective - Stauskis, Gintaras; Jakaitis, Jonas (Landscape Architecture and Art, 2022)
Cities are implementing numerous projects for improving their urban landscapes. The quality of planned landscape interventions is critical for the users and that depends on proper assessment of the projects. After theoretical and empirical research, the paper proposes the framework for quality assessment of landscape architecture projects in relation to sustainability principles. By using the set of pre-determined criteria and relevant indicators the paper offers triple-level multicriteria decision-making tool for assessing the projects aiming at refurbishing, regenerating or conserving the existing parks and gardens, urban open spaces, cultural landscapes and urban infrastructure landscapes by the professional experts. The results of assessing the urban open space refurbishment projects have demonstrated that the proposed solution is fit for setting the participatory quality assessment platform with involvement of stakeholders for comparing the proposals, identifying their advances and shortages, also figuring out the dominating design trends. The results suggest that each phase of project development has a significant impact on the quality of the process and the overall assessment result. Authors and clients should pay special attention to landscape perception values.